What resists concrete? - Cruz, Rhuan (Revista do Colóquio, 2025)
The visual essay "What Resists Concrete?" reflects on the relationship between city and nature, questioning how the urban, marked by rigid and artificial forms, coexists with the organic. The observation focuses on the fissures where life resists and infiltrates, revealing tensions between integration and exclusion. The images do not seek answers, but invite us to perceive the urban as a space of mixture, transformation, and coexistence between different forms of life.
Keywords: visual architecture; econarrative; photography